PERSPEKTIF HUKUM ISLAM MENGENAI PERNIKAHAN DINI AKIBAT SANKSI ADAT DI DESA POWELUA KECAMATAN BANAWA TENGAH KABUPATEN DONGGALA - M Iksan (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
This paper discusses early marriage due to Kaili's customary sanctions in the perspective of Islamic law (Case Study of Powelua Village, Banawa Tengah District, Donggala Regency). The problem to be examined in this research is how early marriage due to kaili customary sanctions in Powelua Village, Kec. Central Banawa District. Donggala and how is the perspective of Islamic law regarding early marriage due to kaili customary sanctions in Powelua Village, Kec. Central Banawa District. Donggala. The research method used in this research is a type of qualitative research, namely the type of research used to examine the conditions of natural objects. The results showed that, early marriage due to customary sanctions (adat ni soko ni po porongo or being arrested by marriage) in Poweluwa Village was already in effect before the spread of Islam in Central Sulawesi in particular, this customary sanction is an inviolable customary sanction starting from ancient times to the present. Marriage due to customary sanctions does not only occur for those who are brought age but marriages due to this customary sanction do not know the age of anyone who is found to have violated customary sanctions so there are only two options, namely paying a fine (givu) or having a marriage (ni soko ni po porongo)